Large Sacrococcygeal Teratoma in Fetus and Newborn: Clinical Case and Review - Butylkina, Jekaterina; Volochovič , Jelena (Lietuvos chirurgija, 2022)
We present a clinical case of fetal and neonatal large sacrococcygeal teratoma. Sacrococcygeal teratoma mostly found in neonates, infant, and children below 4 years old and is more common in girls than boys. Antenatal fetus ultrasound is the main diagnostic method.  Antenatal diagnosis is very important making pregnancy care plan, time and method of delivery also to prevent fetal and neonatal death. Complete excision of the sacrococcygeal teratoma, including the coccyx, remains the mainstay of treatment. Patient's birth mother gives consent for information about the patient (photograph and article) to appear in a journal article.
Keywords: Prenatal fetal ultrasound; sacrococcygeal teratoma; caesarean section; neonatal surgery